Formulatıon Of Busıness Strategıes To Form A Learnıng Organızatıon at PT. XYZ - Indra Gunawan; Ratri Wahyuningtyas (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
The refined sugar processing industry is crucial for a nation's economy as it ensures the continuous availability of sugar for the food, beverage, and pharmaceutical industries, both domestically and internationally, leading to increased demand. Data indicates an annual increase of around 200,000 metric tons for domestic production in Indonesia. To meet this growing demand and industry changes, companies must seize opportunities by becoming learning organizations. This study evaluates the formation of a learning organization at PT. XYZ, examining external factors like politics, economy, society, and technology, and internal factors such as personal mastery, mental models, shared vision, team learning, and systemic thinking. The process uses SWOT analysis for both external and internal factors. Using a case study method, data were collected through in-depth interviews, observation, and secondary data. Interviewees included three individuals: a Factory Manager, a Division Head, a Manager, and a Section Head, focusing on both external and internal factors. The descriptive qualitative method revealed nine strategies, analyzed using EFE, IFE, IE, and SWOT matrices, and prioritized with the Quantitative Strategic Planning Matrix (QSPM). The highest priority strategy was team learning optimization with PDCA, QCC, CFT (Improvement), and Performance Review, Reward & Punishment, scoring a STAS of 3.93. This research offers evaluation and strategic guidance for forming learning organizations, supporting companies in capturing market growth opportunities and adapting to changes.